Analog Circuit Design Scalable Analog Circuit Design, High Speed D/A Converters, RF Power Amplifiers - Huijsing, Johan H.; Steyaert, Michiel.; Roermund, Arthur van. (Springer US, 2002)
This book contains the revised contributions of the 18 tutorial speakers at the tenth AACD 2001 in Noordwijk, the Netherlands, April 24-26. The conference was organized by Marcel Pelgrom, Philips Research Eindhoven, and Ed van Tuijl, Philips Research Eindhoven and Twente University, Enschede, the Netherlands. The program committee consisted of: Johan Huijsing, Delft University of Technology Arthur van Roermund, Eindhoven University of Technology Michiel Steyaert, Catholic University of Leuven The program was concentrated around three main topics in analog circuit design. Each of these topics has been covered by six papers. The three main topics are: Scalable Analog Circuit Design High-Speed D/A Converters RF Power Amplifiers Other topics covered before in this series: 2000 High-Speed Analog-to-Digital Converters Mixed Signal Design PLLỚ"s and Synthesizers 1999 XDSL and other Communication Systems RF MOST Models Integrated Filters and Oscillators 1998 1-Volt- Electronics Mixed-Mode Systems Low-Noise and RF Power Amplifiers for Telecommunication vii viii 1997 RF A-D Converters Sensor and Actuator Interfaces Low-Noise Oscillators, PLLỚ"s and Synthesizers 1996 RF CMOS Circuit Design Bandpass Sigma Delta and other Converters Translinear Circuits 1995 Low-Noise, Low-Power, Low-Voltage Mixed Mode with CAD Trials Voltage, Current and Time References 1994 Low-Power Low Voltage Integrated Filters Smart power 1993 Mixed-Mode A/D Design Sensor Interfaces Communications Circuits 1992 Op Amps ADCỚ"s Analog CAD We hope to serve the analog design community with these series of books and plan to continue this series in the future. Johan H.